افسانہ اورپاکستانی تہذیب و معاشرت : حمید شاہد کی افسانوی کائنات کا مطالعہ: Fiction and Pakistani Culture and Society: A Study of Hameed Shahid's Fictional Universe (Al-Qamar, 2022)
Muhammad Hameed Shahid is an important name in the list of modern fiction writers. He belongs to the generation of fiction writers who adopted the art of fiction writing in the beginning of the eighth half of the last century. He tried to highlight the individual identity of the Pakistani person. He has also highlighted the political and social issues after 9/11 in his fiction based on his observational experience. He is one of the fiction writers who have proved their excellence in both the fields of creation and criticism of fiction. In this article, an analytical study of his fiction writing is presented.
Keywords: Modern fiction; Generation; Fiction writers; Individual identity; Pakistani fiction